MOHS SURGERY: UPDATES ON THE TECHNIQUE FOR REMOVING SKIN CANCERS - Pedro do Valle Varela, João; Gava, Lara; Oliveira Gil de Almeida, Yasmin; Pedro Forechi Rodrigues, João; Cruz Orsi, Verena; Molina Loureiro, Juliana; Miranda Nobre, Julia; Salvadora Cunha Brito, Shaira; Vita de Sá, Júlia; Luiz Teixeira Fully, Fabio (Health and Society, 2024)
Mohs surgery is a highly specialized procedure used to treat skin cancer, especially basal cell carcinoma and squamous cell carcinoma. This technique is known for its high cure rate and preservation of healthy tissue around the affected area. This study aims to review and address the most recent updates in the Mohs surgery technique, including advances in equipment and instruments, improved treatment protocols and post-surgical reconstruction techniques, while also discussing the growing importance of this procedure in contemporary dermatological practice and its positive impact on patients’ quality of life. Mohs surgery involves the surgical removal of thin layers of cancerous tissue, followed by immediate microscopic analysis of the margins of the removed tissue. This allows precise identification of the tumor margins, ensuring complete removal of the cancer while preserving as much healthy tissue as possible. Recent updates to the technique include the use of advanced imaging techniques, such as dermoscopy and confocal microscopy, to aid in the precise identification of tumor margins prior to surgery. In addition, the development of more effective surgical reconstruction methods has improved aesthetic and functional results for patients. It is therefore concluded that Mohs surgery remains an effective option for the treatment of skin cancer, offering high cure rates and preservation of healthy tissue. Updates to the technique, including improvements in diagnostic accuracy and reconstruction options, have contributed to increasingly better results for patients undergoing this procedure.